Floating Currencies, Gold, and SDR's : Some Recent Legal Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1976)
This paper outlines legal developments related to floating currencies, gold, and special drawing rights (SDRs) in the IMF. The Articles of the Fund require each member to establish a par value for its currency in terms of gold as a common denominator. Alternatively, the par value may be expressed in terms of the U.S. dollar of the weight and fineness in effect on July 1, 1944, the effect of which is simply to express the par value indirectly in terms of gold. In this paper, application of existing provisions and valuation of the SDR are discussed in detail, and the new provisions and practices are also elaborated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Currency Of A Participant; Frankfurt Exchange Market; Intervention Currency; PAM; Representative Rate; United States